Theory of resonant inelastic x-ray scattering by collective magnetic excitations - Haverkort, Maurits W. (Arxiv, 2010)
I present a tractable theory for the Resonant Inelastic X-ray Scattering (RIXS) spectral function of magnons. The low-energy transition operator is written as a product of local spin operators times fundamental x-ray absorption spectra. This leads to simple selection rules for the magnetic cross section. The scattering cross section linear (quadratic) in spin operators is proportional to the magnetic circular (linear) dichroic absorption. RIXS is a novel tool to measure magnetic quasi particles (magnons) and the incoherent spectral weight, as well as multiple magnons up to very high energy losses, in small samples, thin films and multilayers, complementary to Neutron scattering.